The Mediating Influence of Relationship Marketing, Customer Satisfaction And Service Quality On Retention Guarantee Recipients In Credit Guarantee Companies - Saleh, Rusdi; Ariyanti, Maya (Publisher Cv. Inara, 2025)
This study aims to examine the effect of market orientation and sales orientation on the retention of guarantee recipients, mediated by relationship marketing, customer satisfaction, and service quality in credit guarantee companies. This study also seeks to determine the extent to which guarantee recipients evaluate these variables and how they are related in shaping retention toward the guarantee services provided. The method used in this study is a quantitative approach with descriptive and causal objectives. The research was conducted using a cross-sectional design through the distribution of questionnaires to credit guarantee recipients. Data were analyzed using Structural Equation Modeling (SEM) to test the relationships between variables. The results indicate that relationship marketing, service quality, and customer satisfaction play a significant role in shaping the retention of guarantee recipients. Specifically, the variables of service quality and customer satisfaction were found to act as mediators that strengthen the relationship between market orientation and sales toward customer retention. The findings of this study provide recommendations for PT Jamkrindo to prioritize strengthening relationship marketing and improving service quality as key strategies in maintaining the loyalty of guarantee recipients. These findings can also serve as a reference for regulators, KUR disbursing banks, and other financial institutions in developing policy frameworks and service synergies oriented toward long-term sustainability.